The effect of sucralfate-containing ointment on quality of life in people with symptoms associated with haemorrhoidal disease and its complications: the results of the EMOCARE survey - Giua, Corrado; Minerba, Luigi; Piras, Antonio; Floris, Nicolina; Romano, Flora; SIFAC, Group (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: A rectal ointment containing 3% of sucralfate and herbal extracts (calendula, witch hazel leaf (hamamelis), chamomile), became available in Italy in 2019 for the treatment of symptoms associated with haemorrhoidal disease. This survey evaluated the effect of the mentioned sucralfate ointment, on quality of life (QoL) and symptom frequency in participants seeking treatment for haemorrhoidal disease from community pharmacies in Italy.Methods: EMOCARE was a multicentre prospective survey conducted at community pharmacies in Italy. Eligible participants (≥18 years) were those with haemorrhoidal symptoms in the last 7 days and were willing to initiate a treatment with the sucralfate ointment and herbal extracts (calendula, witch hazel leaf (hamamelis), chamomile). A survey was administered by the investigating pharmacists at the beginning and end (~14 days) of treatment. The primary endpoint was the change in HEMO-FISS-QoL scores.Results: Of the 290 (mean age 53.1 years old; 58.3% female) enrolled, 287 attended the follow-up visit. After a mean duration of 13 days, the sucralfate ointment significantly improved total HEMO-FISS-QoL scores (mean change from baseline: –10.41; 95%CI –11.95, –8.86; P